پی ٹی وی کوئٹہ؛ براہوئی و بلوچی ڈرامہ غاک: The Brahui and Balochi Drama from PTV Quetta - Farooq, Ummar; Shahwani, Abdul Hameed (Al-Burz, 2016)
This research article refers the Brahui and Balochi dramas telecasted from the Pakistan Television Quetta Centre. This article tells how and when the drama in these both languages got started it further leads that in folk literature of both the languages did the genre of drama had any presence or not. In spite of the dramas telecasted by PTV Quetta Centre Balochi short films made at private sector are also discussed. The main purpose of this article is to collect the scattered material of the Brahui and Balochi dramas and to present them for the new researchers of drama.